Pemetaan Tingkat Kebisingan Pada Jam Sepi Akibat Aktivitas Transportasi Di Simpang Tabek Gadang Pekanbaru - Wahyu Akmal Rinaldi; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The increase in ownership of motorized vehicles has resulted in increased transportation activities. The tendency to increase the number of motorized vehicles operating will increase the traffic load, one example of which is the increase in noise intensity. This study aims to measure noise intensity and map noise at peak hours due to transportation activities that occur at the Tabek Gadang intersection, Pekanbaru City by taking data in the form of noise data and several other traffic variables such as vehicle volume. This research was conducted using a Sound Level Meter (SLM) for 2 days, namely on Monday which represents peak hours and Sunday which represents vehicle quiet hours. The results showed that from 24 measurement points the highest noise level was 96,86 dB which was the point with high traffic volume and the lowest noise level was 76,58 dB which had low traffic volume. Noise mapping using the Surfer 11 software program. From this study it can also be concluded that the greater the volume of the vehicle, the lower the vehicle speed, resulting in a high noise level, and vice versa so that the volume of the vehicle is directly proportional to the noise level, while the speed of the vehicle is inversely proportional to the level of noise. Keywords: Noise, Traffic, Peak Hours, Tabek Gadang Intersection